Symptoms consistent with influenza-like illness in those who tested negative for COVID-19 in England : Coronavirus (COVID- 19) Infection Survey, UK.: Coronavirus (COVID- 19) Infection Survey, UK. (19th December 2022) - Unknown
No abstract available